Islamic Economic Criticists Toward The Indonesian Government Of Rice Policy - Ahmad Fatoni; Kurnia Dwi Sari Utami; Befita Puspisanti (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2020)
Indonesia is currently faced with a condition of declining rice productivity which causes the Indonesian government to import rice from various countries. Looking at this problem, Islamic economics has its own norms, such as not eating before being hungry and stopping before being full. Moreover, there is no Islamic teaching that requires the consumption of rice as the staple food of the community. Referring to the above concept, Indonesian people can use alternative staple foods such as sweet potatoes, corn, sago and various other foods to replace rice, which is very limited and expensive. Besides that, it also takes advantage of media distribution issues such as zakat, waqf, and inheritance. The discussion this time focuses on waqf in which Indonesia's position as the country with the largest waqf in the world with a potential land use of 268,653.67 hectares spread over 366,595 locations throughout Indonesia. It can be allocated to overcome food shortages in Indonesia at this time.